2009
DOI: 10.1051/0004-6361/200912120
|View full text |Cite
|
Sign up to set email alerts
|

Protostellar collapse: rotation and disk formation

Abstract: We present some important conclusions from models of the collapse of rotating molecular cloud cores with axial symmetry, corresponding to the evolution of young stellar objects from class 0 to the beginning of class I. There are three main findings of the calculations: (1) the typical timescale for building up a preplanetary disk, which was found to be of the order of one free-fall time decisively shorter than the widely assumed timescale related to the so-called "inside-out collapse"; (2) redistribution of an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Calcium-aluminum-rich inclusions (CAIs) are the oldest solar system solids dated (Amelin et al 2002, Bouvier & Wadhwa 2010) and believed to have formed when the Sun was a class 0 or class I protostar (e.g., Krot et al 2009;Tscharnuter et al 2009) though Ciesla (2010 argued that most CAIs found in meteorites formed at the time that the solar nebula stopped accreting (MacPherson et al 1995, Jacobsen et al 2008, Makide et al 2009a. CAIs with low ( 26 Al/ 27 Al) 0 , <<5×10 −6 , are very rare (Makide et al 2009a, Sahijpal & Goswami 1998, Liu et al 2009), except in CH carbonaceous chondrites where they are dominant ).…”
Section: Al In Solar Corundum Grains"mentioning
confidence: 99%
“…Calcium-aluminum-rich inclusions (CAIs) are the oldest solar system solids dated (Amelin et al 2002, Bouvier & Wadhwa 2010) and believed to have formed when the Sun was a class 0 or class I protostar (e.g., Krot et al 2009;Tscharnuter et al 2009) though Ciesla (2010 argued that most CAIs found in meteorites formed at the time that the solar nebula stopped accreting (MacPherson et al 1995, Jacobsen et al 2008, Makide et al 2009a. CAIs with low ( 26 Al/ 27 Al) 0 , <<5×10 −6 , are very rare (Makide et al 2009a, Sahijpal & Goswami 1998, Liu et al 2009), except in CH carbonaceous chondrites where they are dominant ).…”
Section: Al In Solar Corundum Grains"mentioning
confidence: 99%
“…Two-dimensional studies were also able to reach this point with a much higher spatial resolution at the center and a more realistic equation of state (Tscharnuter 1987;Tscharnuter et al 2009). Going beyond radiation hydrodynamics, Tomida et al (2010) investigated the additional influence of magnetic fields on the structure and evolution of the first core, but did not cover the second collapse.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent one‐dimensional (e.g. Masunaga & Inutsuka 2000) and two‐dimensional (Tscharnuter 1987; Tscharnuter et al 2009) calculations have not changed this qualitative picture substantially, although the latter have allowed the disc‐like structure of rotating first cores to be studied.…”
Section: Introductionmentioning
confidence: 99%